The Pattern of Heavy Metals Distribution in Time Chronosequence of Ex-Tin Mining Ponds in Bangka Regency, Indonesia - Andri Kurniawan; Oedjijono Oedjijono; Tamad Tamad; Uyi Sulaeman (Universitas Gadjah Mada, 2019)
The heavy metals distribution of ex-tin mining ponds were investigated. The time chronosequence was determined at the pond of age < 1 year (Station A), the pond of age 5–10 years (Station B), and the pond of age > 15 years (Station C). The results showed sixteen heavy metals of As, Co, Cu, Cr, Fe, Ga, Hf, Sn, Ta, Te, Th, Mn, Ni, Pb, Zn, and V could be detected in the ponds. The metals such as As, Co, Cu, Ga, Mn, Ni, Pb, Th, and Zn in Station C showed higher concentration compared to the Station A and Station B. The metals such as Cr, Fe, Hf, Sn, Ta, Te, and V in Station A and Station B showed higher concentration compared to the Station C. The positive, negative, and dynamic correlation pattern could be found in distribution of heavy metal to time chronosequence. The concentration of Ta and V showed a positive correlation because their concentration decrease, whereas concentration of As, Cu, Ga, Mn, and Zn showed a negative correlation because their concentration increase along in time chronosequence. The dynamic correlation could be found that concentration of Co, Ni, Pb, Sn, and Th decrease from Station A to Station B and then increase in Station C, whereas concentration of Cr, Fe, Hf, and Te increase from Station A to Station B and then decrease in Station C.